Morpho (Morpho) helenor (Cramer) (Lepidoptera, Nymphalidae, Morphinae) in Bolivia: Geographical distribution and ecological plasticity, with a description of a new subspecies - Gareca, Yuvinka; Blandin, Patrick (Zootaxa, 2011)
The geographical distribution of Morpho helenor (Cramer) in Bolivia is mapped from the study of specimens preserved in Bolivian and foreign collections, and from recent field studies in various ecoregions. One subspecies, M. h. theodorus Fruhstorfer, inhabits Amazonian moist forests in the western and northern parts of the country. Another subspecies, M. h. coelestis Butler, is common in moist cloud forests (Bolivian Yungas), but also occurs to the North and North-East. We describe a new subspecies, M. h. prometa ssp. nov., from Southern Andean Yungas. Transition zones between theodorus and coelestis are highlighted, where specimens exhibiting intermediate phenotypes were collected. The pattern of geographic transition from M. h. coelestis to M. h. prometa needs to be documented. M. h. prometa inhabits sub-humid, semideciduous forests, whereas M. h. theodorus and M. h. coelestis live in rainforests. M. h. coelestis populations are found from less than 100 m to more than 1600 m a.s.l.; M. h. theodorus has been collected at more than 1000 m a.s.l.; and M. h. prometa between 500 m and 1400 m a.s.l.. Therefore, Bolivian M. helenor populations are distributed throughout a wide range of ecological contexts: we discuss the habitat plasticity of the species in light of available knowledge of its geographical distribution and habitats in the Neotropical Region.